Are the C-reactive protein/albumin ratio (CAR), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (NLR) novel inflammatory biomarkers in the early diagnosis of postoperative complications after laparoscopic sleeve gastrectomy?. Issue 5 (September 2020) - Bora Makal, Gül; Yıldırım, Osman
Highlights: New inflammatory markers in the early detection of post bariatric complications. CRP-to-albumin, neutrophil-to-lymphocyte, and platelet-to-lymphocyte ratios. Preoperative risk factor for the development of post bariatric complications. Abstract: Purpose: C-reactive protein/albumin ratio (CAR), neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are new generation inflammatory markers that have been investigated for use in determining disease prognosis or postoperative morbidity and mortality after many open surgeries. The aim of this study is to investigate the efficacy of CAR, NLR, and PLR on the early detection of postoperative complications (POC) after laparoscopic sleeve gastrectomy (LSG). Material-method: The study included 448 patients, 16–65 years of age, who underwent LSG between 2015 and 2019. C-reactive protein (CRP) and albumin levels were measured on postoperative day 1 and 3 and CAR values were obtained. NLR and PLR values were evaluated preoperatively and on postoperative day 1 and 3. Statistical analyses were performed using the SPSS version 21.0 and MedCalc. Results: A total of 326 patients with a mean age of 37 ± 11 years were analyzed. Both CAR1 and CAR3 values were correlated with the development of complications (r = 0.3, r = 0.3, respectively p < 0.001). Pre-op NLR value was found to be a significant risk factor on complication development (OR = 1.943, p = 0.043). The cut-off value for CAR1 and CAR3 were found as 0.78 and 1.25 mg/dL in ROC analysis (AUC = 0.808, AUC = 0.832, respectively). PLR3 value was diagnostic among other PLR values in the determination of POC (AUC = 0.703 Youden index = 0.36 p = 0.014). Conclusion: The most significant diagnostic value for the determination of POC was CAR3. It was followed by CAR1, CRP3, CRP1, and PLR3 values. Only preoperative NLR was found as a risk factor for the development of POC.